PERKEMBANGAN DAN PEMEROLEHAN BAHASA ANAK - Enjang Burhanudin Yusuf (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Children in acquiring languages pass through a processwhich is unique, step by step, continuous, and flourish until gaining theperfect ability. Along with the physical deelopment, children experienceintellectual and mental growth including language intelligence. Languageacquisition is defined as children’s way in acquiring their first languageor mother language naturally and unconsciously, not formally so thatthey have good language skills. Children’s language development fromnewborn phase to its perfection occurs toward almost all children with thesimilar steps. Children’s language development continues to its perfectionalong with their extensive asociation and interaction with their surroudings.Children are motivated intrinsically or extrinsically to keep deepening theirlanguage skills because with their language they can understand theirsurroundings and develop their ability. There are some opinions relatedto how chidren acquie their first language –Behaviorism, Nativism ormentalism, Cognitivism, Interactionism, and functional theory. Each theoryhas various perspectives about how children can obtain their first language.